2019
DOI: 10.1002/term.2853
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1‐activated type 2 dendritic cells promote wound healing and induce fibroblasts to express tenascin c following corneal full‐thickness hydrogel transplantation

Abstract: We showed previously that 1‐ethyl‐3‐(3‐dimethylamino‐propyl)‐carbodiimide hydrochloride (EDC) cross‐linked recombinant human collagen III hydrogels promoted stable regeneration of the human cornea (continued nerve and stromal cell repopulation) for over 4 years. However, as EDC cross linking kinetics were difficult to control, we additionally tested a sterically bulky carbodiimide. Here, we compared the effects of two carbodiimide cross linkers—bulky, aromatic N‐cyclohexyl‐N0‐(2‐morpholinoethyl)‐carbodiimide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Its larger pendent groups can effectively slow down the crosslinking reaction and provide sufficient operating window at room temperature [ 45 ]. More importantly, CMC/NHS crosslinking system has been proven not to participate in the final crosslinked products and toxic-free on the living organization [ 45 , 46 , 56 ]. Therefore, we chose CMC/NHS as the chemical crosslinker to form the first pDCSM-G polymer network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its larger pendent groups can effectively slow down the crosslinking reaction and provide sufficient operating window at room temperature [ 45 ]. More importantly, CMC/NHS crosslinking system has been proven not to participate in the final crosslinked products and toxic-free on the living organization [ 45 , 46 , 56 ]. Therefore, we chose CMC/NHS as the chemical crosslinker to form the first pDCSM-G polymer network.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a decellularized porcine corneal stroma derived hydrogel enabled fast corneal re-epithelialization after gelation at 37 °C [ 44 ], but such hydrogel alone exhibited low transparency and weak mechanical strength. The introduction of N -cyclohexyl- N’ -(2-morpholinoethyl) carbodiimide metho- p -toluenesulfonate/ N -hydroxysuccinimide (CMC/NHS) crosslinker significantly improved the strength of decellularized porcine cornea derived hydrogel at room temperature but did not significantly affect its bioactivity [ 45 , 46 ]. However, collagenase and metalloproteinase [ 47 ] are secreted abundantly during matrix repair, which may prevent the decellularized cornea hydrogel from long-term retention on corneal defect.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that TNTs could be exploited in vivo to deliver immunomodulatory protein which could either inhibit or promote inflammation. In vitro studies provide the evidence for the presence of tenascin-C in TNTs which are indication for their critical role in tissue remodeling ( 46 ).…”
Section: Role Of Tnts In Ocular Tissuesmentioning
confidence: 99%
“…2018 [158] Collagen hydrogels, 2 different crosslinked collagen hydrogels Mouse Regulate secretion of Tenascin c from fibroblasts. 2019 [159] Collagen Crosslinked with PRA Rabbit Remodeling of corneal epithelium and stroma. 2019 [61] Collagen vitrigel containing biomimetic synthetic Bowman's membrane and Stromal layer.…”
Section: B) Material(s) Animal Model Outcomes Yearmentioning
confidence: 99%